2005
DOI: 10.1158/1078-0432.ccr-04-1560
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Plasma Interleukin-6 Levels in Patients with Metastatic Hormone-Refractory Prostate Cancer: Results from Cancer and Leukemia Group B 9480

Abstract: Interleukin-6 signaling can activate androgen receptor in a ligand-independent manner and may play an important functional role in hormone-refractory prostate cancer (HRCaP) progression and patient survival. Plasma and serum IL-6 levels have been associated with prostate cancer progression in several small studies. In order to evaluate its prognostic significance in metastatic HRCaP patients, we measured IL-6 in plasma collected at baseline from patients in a large cooperative group study [Cancer and Leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(111 citation statements)
references
References 37 publications
3
105
1
2
Order By: Relevance
“…Interleukin-6 (IL-6)-hepcidin axis that regulates iron metabolism is one of the mechanisms which explain our finding of low iron levels in patients with poorer prognosis. Prostate cancer patients with poorer prognosis have higher circulating IL-6 levels (Michalaki et al, 2004;George et al, 2005). It is known that the cytokine leads hepcidin generation in liver (Ganz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 (IL-6)-hepcidin axis that regulates iron metabolism is one of the mechanisms which explain our finding of low iron levels in patients with poorer prognosis. Prostate cancer patients with poorer prognosis have higher circulating IL-6 levels (Michalaki et al, 2004;George et al, 2005). It is known that the cytokine leads hepcidin generation in liver (Ganz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged treatment with IL6 results in generations of sublines that express a more malignant prostate phenotype (Culig 2011). Previous studies have shown that plasma IL6 levels have prognostic significance in patients with metastatic hormone-refractory prostate cancer (George et al 2005). An increase in serum cytokines including IL6 was found in cachectic patients with prostate carcinoma, and immunostaining levels of IL6 and its receptor increased with Gleason score (Pfitzenmaier et al 2003, Royuela et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate dehydrogenase levels may be a marker for tumour burden (Smaletz et al, 2002;George et al, 2005). It was observed that patients experienced a decrease in their LDH levels during treatment.…”
Section: Discussionmentioning
confidence: 99%